Real-world database analysis of the characteristics and treatment patterns of patients with endometrial cancer in Japan. (3rd July 2021) - Akada, Keishi; Koyama, Noriyuki; Miura, Takuma; Fukunaga, Eiji; Miura, Yuji; Aoshima, Ken; Fujiwara, Keiichi
Abstract: Objective: The aim was to identify the characteristics and treatment patterns of early and advanced stage endometrial cancer patients using real-world data. Methods: Patients' data extracted from a Japanese health insurance claims database were analyzed. Results: Of the 12, 449 endometrial cancer patients, 74.4% were in stage I, 5.1% in stage II, 12.0% in stage III, and 8.4% in stage IV. Their median age was 60.5 years, higher in advanced stages (III/IV) than in early stages (I/II). Overall, 11, 055 patients (88.8%) underwent surgery, and 4977 patients (40.0%) received post-surgery treatment, including chemotherapy (4441: 35.7%), chemoradiation therapy (379: 3.0%), and radiation therapy (157 patients: 1.3%); 1394 patients (11.2%) were not treated by surgery, and 742 patients (6.0%) received other treatment, with chemotherapy (548: 4.4%), radiation therapy (105: 0.8%), and chemoradiation therapy (89: 0.7%). The rate of patients undergoing surgery decreased, and that receiving chemotherapy increased significantly as cancer stage progressed. Paclitaxel/carboplatin was the most frequent first-line regimen (85.4% of patients), whereas various combination and monotherapy regimens were used as second- and third-line regimens. The most frequent second-line monotherapy was paclitaxel. The rate of monotherapy increased as the treatment line progressed (first-line 3.5%, second-line 22.0%, and third-line 36.4%). Conclusions: The characteristics and treatment patterns of endometrial cancer patients differed between early and advanced stages, as did the chemotherapy regimens among first-, second-, and third-lines. Since various regimens were used for second- and third-line chemotherapies, development of appropriate second- and third-line chemotherapy regimens is warranted. A real-world analysis of cancer patients using a nationwide claims database may be a valuable approach to identifying unmet medical needs.